Epidemiology and Outcomes of Late-Onset Neonatal Sepsis in Preterm Infants in a Tertiary Hospital - Katerina Kaffe; George A. Syrogiannopoulos; Efthimia Petinaki; Maria Goudesidou; Anna Kalaitzi; Antonios Gounaris; Ioanna N. Grivea (Children)
Background/Objective: Late-onset sepsis (LOS), a systemic infection occurring after 72 h of life, is a significant issue of morbidity and mortality in preterm neonates. Nevertheless, in this population, cultures frequently remain negative, even in the presence of typical clinical signs of sepsis. Materials and Methods: This single-center, retrospective study included preterm infants with a birth weight (BW) < 1500 g and/or a gestational age (GA) ≤ 32 weeks, diagnosed with culture-negative LOS (CNLOS) and culture-proven LOS (CPLOS). The study aimed to determine the incidence of these conditions, describe the frequency of isolated pathogens, and compare clinical profiles, antibiotic usage, morbidity, and mortality between these two groups as well as a no-sepsis group. Results: Among 277 infants, 30 (10.8%) had CPLOS, 83 (30%) had CNLOS, and 164 (59.2%) had no sepsis. Significant differences were found between the groups regarding BW, GA, hospitalization duration, morbidity, and mortality (p < 0.001). CNLOS and CPLOS did not differ in terms of mechanical ventilation or central line use. However, CPLOS infants had a higher rate of thrombocytopenia (p < 0.001), inotrope use (p = 0.006), and mortality (p < 0.001) compared to CNLOS infants. The duration of antibiotic treatment was similar between groups [median DOT (IQR): 20 (14–33) vs. 20 (14–35), p = 0.935]. In the CPLOS group, Gram-negative pathogens were isolated in 42.4% of infants, with Klebsiella oxytoca being the most common; Gram-positive organisms in 36.3%; and fungi in 21.2%. Conclusions: LOS, whether culture-proven or not, was associated with neonatal morbidity and mortality. CPLOS was linked to a worse prognosis, while CNLOS was also frequently diagnosed and associated with increased antibiotic use in Neonatal Intensive Care Units (NICUs).